HIERONIMOS, TOPONIMOS, ANTROPONIMOS AND OTHERS IN PAULISTA AGRICULTURE - Pino, Francisco Alberto (Cadernos CERU, 2004)
The farm names in the state of São Paulo, Brazil, are analyzed using agricultural census data. Naming a farm depends on dealing with business or home farming. In the former case the farm names tend to be objective, as a place name or the brand name, mainly for merchandizing reasons. In the latter the names tend to express the farmer ideology, way of life or dreams, in short, his culture. The religious are sacred names, specially catholic, prevailed against all the others (over 40%). So, the most common farm name showed to be St. Anthony (5% of the farms), followed by St. Joseph, St. John and the Brazilian patron madonna. The first non-catholic names is the eight one: Bela Vista (Beautiful View). Personal and family names, specially Portuguese, Spanish, Japanese and Italian ones, are also very common and these were probably given by proud immigrants who became land owners to indicate their new status. As expected, toponyms are usual, indicating the place where the farm is located. There are also Indian names, American country style names, poetical, funny, mythological, and literary names. The television and cinema influence is also observed. It is concluded that strong cultural factors are involved when naming farms and this should be used to understand the farmer decisions and opinions.